Assessing Fiscal Space for Health in the SDG Era : A Different Story - Barroy, Helene (Taylor and Francis, 2018)
Initially defined for overall public purposes, the concept of fiscal space was subsequently developed and adapted for the health sector. In this context, it has been applied in research and policy in over 50 low- and middle-income countries over the past ten years. Building on this vast experience and against the backdrop of shifts in the global health financing landscape in the Sustainable Development Goals (SDG) era, the commentary highlights key lessons and challenges in the approach to assessing potential fiscal space for health. In looking forward, the authors recommend that future fiscal space for health analyses primarily focus on domestic sources, with specific attention to potential expansion from the improved use and performance of public resources. Embedding assessments in national health planning and budgeting processes, with due consideration of the political economy dynamics, will provide a way to inform and impact allocative decisions more effectively.